The Relationship Between Bronchial Patency and Parameters of ECG Supraventricular Component in Children With Bronchial Asthma - Gordina, Alina V.; Egoshina, Ksenia A.; Eliseeva, Tatyana I.; Vinogradova, Nadezhda G.; Ovsyannikov, Dmitry Yu.; Tush, Elena V.; Prakhov, Andrey V.; Daniel-Abu, Mojisola I.; Khaletskaya, Olga V.; Kubysheva, Nailya I. (Frontiers in Pediatrics, 2020)
Background. Uncontrolled asthma (BA) can be complicated by cardiac conduction disturbances and arrhythmias. It is typical mainly for adult asthmatics patients. In asthmatics children the effect of bronchoconstriction on cardiac conduction, including the supraventricular component of the ECG, is currently under discussion. The objective of the research is to analyze ECG parameters of the atrial complex and atrioventricular conduction and to assess their relationship with spirometric indicators in children with BA. Methods. 103 patients with BA from the age of 6 to 17 years were examined. The spirometric parameters were evaluated, including the Tiffeneau index (TI): FEV1/FVC (%), according to the level of which the patient groups were distinguished. Group 1 (G1): with TI more than 85%, (n=15); Group 2 (G2): with TI from 85% to 75%, (n=40); Group 3 (G3): with TI less than 75%, (n=48). The ECG parameters that characterize supraventricular conduction, including the PQ interval (sec) and the sPQ segment (sec), were analyzed. We had calculated relative PQ (rPQ) by the formula rPQ=PQ/PQmed, where PQ is the patient’s PQ, PQmed are the median PQ values of healthy children of age selected. Results. The duration of the PQ in groups G1 and G2 was 0.13[0.11; 0.14] sec; and 0.13[0.12; 0,14] sec, respectively, which is statistically significantly less than in patients of groups G3 - 0,14[0,13; 0.15] sec, p=0.01. The duration of the sPQ segment in children of groups G1 and G2 was also generally shorter than in patients of groups G3, and amounted, respectively, to 0.05[0.04; 0.06] sec, 0.04[0.04; 0.05] sec and 0.06[0.04; 0.07] sec, p=0.02. The rPQ increased progressively as TI decreased and amounted in G1 to 92.9[85.7; 106.3]%, in G2 100.0[92.9; 103.0]%, and in G3 104[100.0; 107.7]%, p=0.009. A statistically significant negative correlation between IT and PQ - r=-0.23, p=0.02; with sPQ - r=-0.20, p=0.045; and with rPQ - r=-0.25, p=0.01 was revealed. Conclusion. A decrease in TI in asthmatics children is associated with a prolongation of the PQ. This may indicate a slowdown in supraventricular conduction in patients with uncontrolled asthma and, thus, be considered as a risk for the formation of subsequent supraventricular arrhythmias.